Advances in Reinforced Soil Structures Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
Soil reinforcement is a very useful technique to construct several cost-effective soil structures in an environmentally friendly and sustainable manner. The most commonly used reinforcement materials are galvanised steel strips, geosynthetics in the form of woven geotextiles, geogrids and geocomposites, and fibres from natural and waste products. In recent years, there have been advances in the area of soil reinforcement, especially in the utilization of the technique in field projects. The researchers have also been working to understand the behaviour of reinforced soil considering the field challenges of reinforced soil structures. This edited volume contains contributions on advances in reinforced soil structures, mainly flexible pavements, footings, embankments, stone columns/piles, and slopes, as covered in the subject areas of geosynthetic engineering and fibre-reinforced soil engineering. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.